1983
DOI: 10.1002/food.2750270808
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed: Constituents and protein products Part 2: Preparation and properties of protein‐enriched products

Abstract: literature is reviewed about the preparation and functional properties$nd application of defatted meals, protein concentrates and isolates of Brassica seeds. Especially the influence of physico-chemical, microbiological and enzymatical treatments is represented on antinutritional compounds, glucosinolates, their splitting products and phytic acid. General classification of processes and productsAs protein-enriched manufactured products from Brassica seed are recognised seed meals, protein concentrates and isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 106 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Hydrolysis contributed to a remarkable improvement in the solubility of CPHs at pH 4.0 and 7.0; however, CPI had the highest solubility at pH 9.0. This may have contributed to the high nitrogen yields that are normally obtained for the isolate under strong alkaline extraction conditions (Mieth et al ., ). The molecular weight range of the hydrolysates as previously described ranged from 6.47–0.027 kDa for Alcalase; 0.711–0.027 for chymotrypsin, 2.45–0.052 kDa for pepsin and 6.75–0.347 kDa for trypsin (Alashi et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Hydrolysis contributed to a remarkable improvement in the solubility of CPHs at pH 4.0 and 7.0; however, CPI had the highest solubility at pH 9.0. This may have contributed to the high nitrogen yields that are normally obtained for the isolate under strong alkaline extraction conditions (Mieth et al ., ). The molecular weight range of the hydrolysates as previously described ranged from 6.47–0.027 kDa for Alcalase; 0.711–0.027 for chymotrypsin, 2.45–0.052 kDa for pepsin and 6.75–0.347 kDa for trypsin (Alashi et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The use of alkali, as shown by Sosulski (1983) and Mieth and others (1983) , produce strong conditions (pH 11 to 12) that were necessary to obtain high nitrogen extraction yield and a high protein extraction rate from canola meal. Tzeng and others (1988a) maintained the pH of the solution by the addition of 50% w/w NaOH solution.…”
Section: Canola Protein Extractionmentioning
confidence: 99%
“…Canola protein was made up of approximately 70% of salt soluble globulins, up to 20% of alcohol soluble prolamins, and 10% to 15% water-soluble albumins. Prolamins in rapeseed exist exclusively as oleosin, the structural proteins associated to the oil bodies ( Mieth and others 1983 ). Klockeman and others (1997) , however, reported that the isolated canola proteins were primarily glutelins and globulins.…”
Section: Canola Protein Extractionmentioning
confidence: 99%
“…While sufficient for adhesive production, extraction of proteins requires additives to improve protein recovery yield . Proteins are able to be isolated from the rapeseed meal using pH-altering solvents and centrifugation. To minimize competition between food and adhesive industries with respect to soy protein, rapeseed proteins in combination with other protein-rich components detail superior adhesion tendencies due to combined protein molecular weight distributions …”
Section: Adhesives Made From Soy and Other Traditional Crop-based Pro...mentioning
confidence: 99%